PARTISIPASI CIVITAS AKADEMIKA DALAM PENGELOLAAN ECO-KAMPUS DAN PEMANFAATAN LIMBAH ORGANIK TUMBUHAN UNTUK PEMBUATAN PUPUK KOMPOS DI LINGKUNGAN KAMPUS UIN RADEN INTAN LAMPUNG - Nasor Nasor; Jasmadi Jasmadi (Pascasarjana IAIN Metro, 2020)
Environmental problems and management efforts are increasingly complex covering various aspects, while human understanding of the environment is still limited. Limited supporting infrastructure and the availability of reliable human resources (HR) are the main factors that need attention. The academic community has great potential in building an integrated, comprehensive and sustainable environmental management. Therefore, it is necessary to develop a concept that can unite all elements in an environmental management system. From this system, it is hoped that it can build awareness about the importance of environmental management. This research takes the type of field research (field research), namely the type of research carried out in a place, namely research conducted in real life. Regarding the data source in this study, the opinions of the campus users are in preserving and protecting the campus environment. The results of the research are efforts to strengthen the participation of campus residents to develop their awareness of environmental preservation towards sustainable development based on the Green Campus concept. Forms of participation of campus residents in environmental preservation are through routine activities in the form of independent, integrated and mutual cooperation as a form of empowerment. In realizing a green, clean, orderly, neat, beautiful and comfortable campus; involving campus residents can participate in accordance with their respective main duties. This reflects the awareness of campus residents in environmental preservation based on the green campus concept of sustainable development.